"Because your dysphoria gets in the way of you…it affects everything." The mental, physical, and relational aspects of navigating body dysphoria and sex for trans masculine people. Issue 1 (23rd February 2022) - Martin, Tristan K.; Coolhart, Deb
Abstract: Research suggests that many trans masculine people experience distress from body dysphoria. Social and medical transition through hormones and gender confirmation surgery offer some relief for body dysphoria; however, trans masculine people may continuously experience the impact of their body dysphoria on sexual experiences. This qualitative study explored the influence of body dysphoria on sexual experiences with 10 trans masculine people using Interpretive Phenomenological Analysis. The first emerging theme included mental negotiation of dysphoria in which participants described a process of having a mind-body connection, experiencing negative mental health outcomes, and continuous thoughts. The next theme was physical negotiation of body dysphoria in which participants described having body discomfort, using testosterone and surgeries to reduce body dysphoria, creating sex boundaries, using prosthetics, exploring masculinity, and self-pleasure. The last theme was relational negotiation of body dysphoria, participants discussed feeling burdened by sharing sexual needs, finding a stronger sexual connection with certain sexual identities, partner pleasing, communication, and receiving support. This study demonstrated that it is crucial for clinicians to understand the connection between body dysphoria and sexual experiences. Allowing a space for trans masculine people to be validated can reduce negative mental health outcomes, build community, and increase resiliency.